THE ROLE OF CORPORATE CULTURE IN THE SUCCESSFUL DEVELOPMENT SYSTEM OF PERSONNEL MANAGEMENT OF ENTERPRISES - SMIHUNOVA, Olena; MYKOLENKO, Inna; ROMANASHENKO, Maryna (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Today, the corporate culture existing in Ukrainian enterprises is very undeveloped, and in some places it has a formal appearance. Heads of domestic enterprises, postponing the formation of corporate culture or generally considering it unnecessary, do not realize the negative impact of this phenomenon on the level of economic security of the personnel system of their enterprises, which as a result restrains their economic development. Increasing the indicators of social and economic activity of enterprises and ensuring their stable and economically safe development requires the formation of a high-level corporate culture. Built on the basis of an integral system of values, the corporate culture of the enterprise is able to act as an effective image tool, forming a high level of staff loyalty on the one hand, and stable partnership relations with the subjects of the external environment on the other. Evaluation of the effectiveness of the corporate culture is determined both by the parameters of the social and psychological climate in the team, and by the satisfaction of the company’s employees with the performance indicators of its work. The article states that it is employees’ awareness of their own role in shaping the overall result of the enterprise that contributes to the growth of their loyalty. The necessity of applying such a personnel policy at the enterprises, which should be based on a balanced system of motivation of the work of the personnel, which as a result will ensure personnel and economic security, is noted. The stages and levels of the formation of corporate culture have been determined, the sequential passage of which allows for the automatic reproduction of corporate behavior by employees. Taking into account the presence of an individual business philosophy, a system of values, principles, rules and norms of behavior, the general features of an organization with a strong corporate culture are singled out. Approaches to the implementation of corporate culture at the enterprise are defined, which are implemented depending on the results of the analysis of the impact of corporate culture on the indicators of the socio-economic efficiency of the enterprise, and taking into account its compliance with the general strategy of the enterprise. At the same time, the influence of the enterprise’s corporate culture on its general strategy should be carried out using a model of comprehensive assessment of the functional, elemental and organizational levels of building corporate culture.